Examining the Model for Forming Religious Character Education through Santri Behavior Traditions in Islamic Boarding Schools - Amirul Muttaqin; Roibin Roibin; Ahmad Barizi; Jamilah Jamilah; Bima Fandi Asy'arie (AL-ISHLAH: Jurnal Pendidikan, 2024)
Islamic boarding schools (IBS) are unique Islamic educational institutions that play a significant role in shaping the character and behavior of santri (students). This study aims to explore the perspectives of kiai (Islamic leaders) in internalizing a character education model within santri traditions amidst the challenges of modernity.This qualitative research employs a phenomenological approach, focusing on field studies conducted at the Annuqayah Islamic Boarding School in Sumenep, East Java. Data collection involved interviews with 10 kiai, providing insights into traditional practices that influence santri character formation.The findings reveal several traditional models that foster character development in santri. These include showing respect to kiai through specific customs like handshaking, communal meals, polite communication, simple attire, maintaining cleanliness, fulfilling worship obligations, respecting guests, displaying diligence in learning, and engaging in unique rituals such as "bersampetan" (communal bathing). These practices strengthen relationships among kiai, ustadz (teachers), santri, and other residents within the IBS environment, creating a harmonious and conducive learning atmosphere.These traditions are integral to character education in IBS, reinforcing values of integrity, ethics, and responsibility. They not only preserve the cultural heritage of Islamic boarding schools but also offer a sustainable model for character building relevant to the modern era.The findings suggest that IBS traditions can serve as an effective framework for character education, addressing contemporary challenges while fostering the development of ethical, responsible, and well-rounded individuals in Islamic education.